Development of an application to improve mental health (A) - Khor, Chin Yi (Nanyang Technological University, 2023)
Mental health is one of the significant problems faced by the world nowadays. According to the World Health Organization (WHO)'s World Mental Health Report, in 2019, about one in every eight people worldwide suffered from mental health disorders. In addition, the COVID-19 pandemic triggered a 25% increase in the global prevalence of anxiety and depression, further worsening mental health around the globe. As the mental health concern grew, most countries developed new mental health information and phone support lines, offering tips to the public on coping measures. At the same time, many countries also increased their funding for mental health services.